Business Intelligence Implementation to Support Data Driven Strategic Decision Making in Digital Organizations - Tessa Handra; Agung Rizky; Mungkap Mangapul Siahaan; Steven Harazaki Lase; Kamal Arif Al-Farouqi (Technomedia Journal, 2026)
Digital transformation has encouraged organizations to generate large volumes of data that must be managed effectively to support strategic decision-making. Business Intelligence has become a solution for integrating, analyzing, and presenting data into valuable information. This study aims to analyze the implementation of Business Intelligence in digital organizations, its role in supporting data-driven strategic decision-making, as well as the benefits and challenges of its implementation. This study used a qualitative method with a literature review approach by examining journals, scientific articles, and other academic publications related to the research topic. The data were analyzed using descriptive qualitative analysis. The results show that the implementation of BI through data warehouses, dashboards, reporting systems, and data analytics can improve operational efficiency, accelerate access to information, and support performance monitoring and business trend analysis more effectively. BI also supports faster and more accurate data-driven decision-making. Business Intelligence plays an important role in supporting strategic data-driven decision-making in digital organizations. However, its implementation still faces challenges related to data quality, information security, limited human resource competencies, and high technology implementation costs.